Implementation of The Project to Strengthen The Profile of Pancasila Students (P5) In The Cupak Gerantang Musical Drama Performance at SMAK Kesuma Mataram - Andhika Rizkika; Duwi Purwati; Gde Agus Mega Saputra; Wahyu Kurnia (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
The Pancasila Student Profile Strengthening Project or commonly abbreviated as P5 is cross-disciplinary learning in observing and thinking about solutions to problems in the surrounding environment to strengthen various competencies in the Pancasila Student Profile. Implementation is carried out flexibly both in terms of content, activities and implementation time. This research aims to determine the implementation and achievements achieved by teachers and students at SMAK Kesuma Mataram in carrying out a project to strengthen the profile of Pancasila (P5) students in the musical drama Cupak Gerantang. This research uses a case study approach with qualitative methods and quantitative methods, using questionnaires as research support. Based on the research results, the application of P5 using musical drama performances as the output of P5 itself is indicated as a good process in instilling the values ​​of the Pancasila dimension among students at school.